Optimalisasi Penggunaan Bahan Ajar Pada Program Pelatihan Calon Pekerja Imigran Indonesia - Felicia Aprilani Marsono; Hety Nurohmah; Abdul Latif Jaohari (Vocational College of Diponegoro University, 2023)
The use of teaching materials is an important aspect in supporting the qualifications of prospective migrant workers who are able to communicate in Japanese. It is intended that prospective migrant workers can take the job selection process in various types of jobs that will be passed. This study aims to optimize the use of Minna no Nihongo teaching materials at the Indonesian Migrant Workers Job Training Center, West Java Disnakertrans. The research method used is descriptive qualitative method with data collection techniques through observation, interviews, and literature study. The research respondents were 17 students of the Indonesian Migrant Workers Job Training Center who were attending the Japanese language training program. The results showed that the use of Minna no Nihongo teaching materials is good, but its use still needs to be optimized. Especially in terms of the percentage of learning related to Japanese speaking skills. Therefore, it is necessary to make some efforts to optimize the use of this teaching material, namely by increasing the percentage of speaking learning to support the ability of prospective migrant workers and adding conversational learning activities (kaiwa) by optimizing interesting themes in Minna no Nihongo.It is hoped that the results of this study can provide benefits for managers of the Indonesian Migrant Workers Job Training Center in improving the quality of Japanese language training programs provided to students. In addition, the results of this study can also be used as a reference for future researchers who are interested in conducting similar research.. Keywords: teaching materials; Japanese; prospective migrant workers